Corporate Governance In India Evolution, Issues And Challenges For The Future (International Journal of Scientific Research and Management (IJSRM), 2014)
This paper compiles a history of the evolution of corporate governance reforms in India and through a survey of existing research, identifies issues that are peculiar to the Indian context and which are not being adequately addressed in the existing corporate governance framework. Lastly, this paper suggests the need for robust research in the field of corporate governance research that would support policy formulation in order to make the next generation of corporate governance reforms more effective for the Indian conditions.